The Role of Variation at AßPP, PSEN1, PSEN2, and MAPT in Late Onset Alzheimer's Disease. - GILL, MICHAEL; LAWLOR, BRIAN (My University, 2011)
Rare mutations in A?PP, PSEN1, and PSEN2 cause uncommon early onset forms of Alzheimer's disease (AD), and common variants in MAPT are associated with risk of other neurodegenerative disorders. We sought to establish whether common genetic variation in these genes confer risk to the common form of AD which occurs later in life (>65 years). We therefore tested single-nucleotide polymorphisms at these loci for association with late-onset AD (LOAD) in a large case-control sample consisting of 3,940 cases and 13,373 controls. Single-marker analysis did not identify any variants that reached genome-wide significance, a result which is supported by other recent genome-wide association studies. However, we did observe a significant association at the MAPT locus using a gene-wide approach (p = 0.009). We also observed suggestive association between AD and the marker rs9468, which defines the H1 haplotype, an extended haplotype that spans the MAPT gene and has previously been implicated in other neurodegenerative disorders including Parkinson's disease, progressive supranuclear palsy, and corticobasal degeneration. In summary common variants at A?PP, PSEN1, and PSEN2 and MAPT are unlikely to make strong contributions to susceptibility for LOAD. However, the gene-wide effect observed at MAPT indicates a possible contribution to disease risk which requires further study.
PUBLISHED
Keywords: Genetics; Alzheimer's disease (AD); Immunology, Inflammation & Infection